The Impact of Availability of Means of Transport on Agricultural Production in Selected European Countries - Rokicki, Tomasz (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2014)
The object of the paper is to determine the relationship between the number of tractors and production results. Seven European countries with diverse land, production and human resources and different natural and topographic conditions were selected by the application of the purposive sampling method and included in the study. The study period spans from 2004 to 2009. In the analysed population, production results were not in correlation with the number of tractors. When examining the relationship only in some selected countries, the author discovered the existence of differences in the correlation between the number of tractors and the value of agricultural production. The resulting correlation values for developed countries were positive, whereas in the case of developing countries, the values were negative. Thus, the number of tractors influences the value of agricultural production in harmonised economies. Nevertheless, we should also consider a number of additional factors, such as price volatility, weather conditions, etc.